Ilha de calor urbana no semiárido: um estudo de caso na cidade de Iguatu/Ceará - Pinheiro, Mayra Alves (2022)
Iguatu, located in the interior of the Northeast region of Brazil, is on the list of the 299 most populous municipalities in Brazil and of the 9 most populous in Ceará, configuring itself as the main economic hub of the Centre-South region of Ceará State, where the most intense occupations of activities take place in the urban area of the municipality. In this context, the present investigation aims to discuss the urban climate composition of a medium-sized city in the Brazilian semi-arid region, as well as the hygrothermal behavior and the thermal sensation, considering that the forms of use and occupation of the soil have direct influence on the modification of the climate of a city. The present research was carried through the following stages: 1 - bibliographical survey - to subsidize the construction of a consistent theoretical framework; 2 - geoenvironmental characterization / basic cartography of the study area 3 - cartographic collections - in order to gather information already produced about the study area, also performing the selection of thermal images; 4 - field work - with primary data survey of temperature values and relative humidity, performed through mobile transects in two distinct seasonal periods; 5 - data analysis and interpretation - performed through human resource and computational tools. The results showed that the temperature difference along the studied points in the two transect routes reached 4.4 °C. The sectors furthest from the urban center were characterized by the lowest temperatures between 25.1 °C and 27.0 °C. The effective temperature index for the rainy period showed that the thermal sensation of the study area varies from 19.1 °C - 22.3 °C (pleasant sensation), and for the dry period, the effective temperature values varied from 23 °C to 25.5 °C (moderately hot feeling). The results corroborate the existence of heat islands (atmospheric and superficial), whose shape, intensity and magnitude depend on several factors of natural and anthropogenic derivations and that they interfere in the thermal sensation in the municipality of Iguatu/CE.